Discovery Products and the Open Archives Initiative Protocol for Metadata Harvesting. Issue 1 (2nd January 2018) - Corrado, Edward M.
ABSTRACT: Discovery products promise to offer library patrons one-stop shopping for library resources. In order to accomplish this, they harvest metadata from various library databases and repositories such as integrated library systems, institutional repositories, and digital libraries. Discovery products then index this metadata along with the metadata for resources from the discovery service into a single product for search. The most common method used to harvest local metadata is the Open Archives Initiative Protocol for Metadata Harvesting (OAI-PMH). This column first looks at discovery, then it describes OAI-PMH and some of the issues involved with effectively harvesting library metadata. COLUMN EDITOR'S NOTES: The "Advances in Library Data and Access" column examines technological advances internal and external to libraries. The focus is on how library data are created and used. The strength of the column is its broad, international focus, and contributors are encouraged to explore issues and recent advances in information technology relevant to their geographical region, as well as the larger, global audience. Interested authors are invited to submit proposals and articles to the column editor atmoulaisonhe@missouri.edu . Please include "IILR Submission" in the subject line of the email.